Cultural Tourism and The Use of Local Wisdom in The Bancakan Salak Galengdowo, East Java - Suksmawati, Herlina; Pabyantara, Dias; Nuryananda, Praja Firdaus (Graduate School, Universitas Brawijaya, 2020)
The research aimed to elaborate on the common value represented by Bancakan Salak of Gelengdowo Village. Qualitative phenomenology was used to obtain a comprehensive understanding of the research problem. The data collection techniques used in this research is observation of both preparation and due day process. The semi-structured interview was conducted with the chief of the committee, local government representation, local youth figure, and two elders while checking the previous studies to get a comprehensive picture. The finding consists of three-part: (1) the preparation stage has substantial collectivism value, (2) the word bancakan finds its intrinsic value in the long tradition of bancakan practice by the community to express their gratitude upon God blessing, (3) the culture of almsgiving reflected in the tumpeng-shaped salak. The community has been practicing those three values since the beginning. Therefore it inspires and reflected in the creation of Bancakan Salak.Keywords: bancakan salak, Galengdowo, local wisdom, social practice.